Cryptocurrency: A panacea for economic growth and sustainability? A critical review of crypto innovation. (July 2022) - Shin, Donghee; Rice, John
Highlights: With the conceptualization of the blockchain as a sociotechnical system, the crypto initiatives in Dubai are examined. Despite proactive drives, new risks, such as privacy, transparency, and security, emerge as critical concerns. Cryptocurrency as a socio-technical system that constitutes new and important objects of social inquiry. Abstract: Distributed ledger technology is highlighted as a solid tool to address social and ecological challenges. Cryptocurrency is seen as a network with a socio-technical structure since the systems are composed of technical infrastructure and the social relations between users of the crypto ecosystem. The sociopolitical ramifications of cryptocurrency are critically assessed to identify key features and conceptualize issues to unlock opportunities to guarantee a sociotechnical approach to blockchains. Despite progressive initiatives, a series of challenges, such as trust, cybersecurity, and scalability, have emerged as cryptocurrency begins to develop its full potential. With these issues, sociotechnical concerns have surfaced regarding how to respond to the possible consequences that such a policy choice would entail, how to govern the crypto economy, and how to create a sustainable crypto ecosystem. We argue that cryptocurrency is a socio-technical system that constitutes new and important objects of social inquiry that must be addressed beyond the myopic context of a financial asset.